Trends in hepatitis B virus testing practices and management in HIV clinics across sub- Saharan Africa - Coffie, Patrick A.; Egger, Matthias; Vinikoor, Michael J.; Zannou, Marcel; Diero, Lameck; Patassi, Akouda; Kuniholm, Mark H.; Seydi, Moussa; Bado, Guillaume; Ocama, Ponsiano; Wandeler, Gilles (BMC infectious diseases, 2017)
Approximately 8% of HIV-infected individuals are co-infected with hepatitis B virus (HBV) in sub-Saharan Africa (SSA). Knowledge of HBV status is important to guide optimal selection of antiretroviral therapy (ART) and monitor/prevent liver-related complications. We describe changes in testing practices and management of HBV infection over a 3-year period in HIV clinics across SSA. Methods: A medical chart review was conducted in large urban HIV treatment centers in Côte d’Ivoire (3 sites), Benin, Burkina Faso, Cameroon, Kenya, Senegal, South Africa, Togo, Uganda and Zambia (1 site each). Of the patients who started ART between 2010 and 2012, 100 per year were randomly selected from each clinic. Demographic, clinical and laboratory information as well as individual treatment histories were collected using a standardized questionnaire. We examined changes over time in the proportion of patients screened for HBV infection (HBV surface antigen [HBsAg]-positivity), identified predictors of HBV testing using logistic regression, and assessed the proportion of patients initiating a tenofovir (TDF)-containing ART regimen. Results: Overall, 3579 charts of patients initiating ART (64.4% female, median age 37 years) were reviewed in 12 clinics. The proportion of patients screened for HBsAg increased from 17.8% in 2010 to 24.4% in 2012 overall, and ranged from 0.7% in Kenya to 96% in South Africa. In multivariable analyses, age and region were associated with HBsAg screening. Among 759 individuals tested, 88 (11.6%; 95% confidence interval [CI] 9.4–14.1) were HBV-infected, of whom 71 (80.7%) received a TDF-containing ART regimen. HBsAg-positive individuals were twice as likely to receive a TDF-containing first-line ART regimen compared to HBsAg-negative patients (80.7% vs. 40.3%, p < 0.001). The proportion of patients on TDF-containing ART increased from 57.9% in 2010 to 90.2% in 2012 in HIV/HBV-co-infected patients (Chi-2 test for trend: p = 0.01). Only 114 (5.0%) patients were screened for anti-HCV antibodies and one of them (0.9%, 95% CI 0.02–4.79) had a confirmed HCV infection. Conclusions: The systematic screening for HBV infection in HIV-positive patients before ART initiation was limited in most African countries and its uptake varied widely across clinics. Overall, the prescription of TDF increased over time, with 90% of HIV/HBV-coinfected patients receiving this drug in 2012.
Keywords: Hepatitis B virus testing; HIV clinics; Sub- Saharan Africa